2016
DOI: 10.1113/jp271441
|View full text |Cite
|
Sign up to set email alerts
|

Neural FFA3 activation inversely regulates anion secretion evoked by nicotinic ACh receptor activation in rat proximal colon

Abstract: Key pointsr Luminal short-chain fatty acids (SCFAs) influence gut physiological function via SCFA receptors and transporters.r The contribution of an SCFA receptor, free fatty acid receptor (FFA)3, to the enteric nervous system is unknown. AbstractThe proximal colonic mucosa is constantly exposed to high concentrations of microbially-produced short-chain fatty acids (SCFAs). Although luminal SCFAs evoke electrogenic anion secretion and smooth muscle contractility via neural and non-neural cholinergic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 53 publications
6
55
0
Order By: Relevance
“…In a similar experimental model to that of the present study, it was shown that luminal perfusion of acetate increased duodenal bicarbonate secretion in a dose-dependent manner via dual mechanisms involving the activation of both FFA2 receptors expressed on enterochromaffin cells and FFA3 receptors expressed on endocrine L cells. Supporting this notion is that apical FFA3 receptors expressed by L cells increase duodenal bicarbonate secretion via release of GLP-1/GLP-2 (Tolhurst et al 2012;Akiba et al 2015), and activation of neural FFA3 receptors suppresses nicotinic acetylcholine receptor-stimulated Cl − secretion in rat proximal colon (Kaji et al 2016). An interesting observation of the present study was that the I.V.…”
Section: Discussionsupporting
confidence: 71%
“…In a similar experimental model to that of the present study, it was shown that luminal perfusion of acetate increased duodenal bicarbonate secretion in a dose-dependent manner via dual mechanisms involving the activation of both FFA2 receptors expressed on enterochromaffin cells and FFA3 receptors expressed on endocrine L cells. Supporting this notion is that apical FFA3 receptors expressed by L cells increase duodenal bicarbonate secretion via release of GLP-1/GLP-2 (Tolhurst et al 2012;Akiba et al 2015), and activation of neural FFA3 receptors suppresses nicotinic acetylcholine receptor-stimulated Cl − secretion in rat proximal colon (Kaji et al 2016). An interesting observation of the present study was that the I.V.…”
Section: Discussionsupporting
confidence: 71%
“…FFA3 activation inhibits cholinergic-mediated ion secretion [27] and colonic motility [28] via direct neural FFA3 activation. We thus examined the effect of ip injection of AR420626 on IND-induced intestinal ulcer scores.…”
Section: Resultsmentioning
confidence: 99%
“…FFA3 is expressed on L cells [21], but also on enteric nerves [27,37]. Neural FFA3 activation inversely regulates nicotinic acetylcholine receptor-mediated anion secretion [27] and motility [28] in rat proximal colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that FFA3 is expressed on cholinergic nerves located in the mucosal and submucosal plexus of rat proximal colon, and that FFA3 activation suppressed nAChR‐mediated anion secretion, possibly through the inhibition of neural ACh release . Myenteric neurons expressed FFA3 more abundantly, suggesting that FFA3 significantly contributes to colonic motility regulation .…”
Section: Introductionmentioning
confidence: 99%